Planting method, nitrogen fertilization and inoculation for diazotrophic bacteria for Cantaloupe melon plants - Vendruscolo, Eduardo Pradi; Oliveira, Paulo Ricardo; Campos, Luiz Fernandes Cardoso; Seleguini, Alexsander; Lima, Sebastião Ferreira de (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The objective of this study was to evaluate the effects on plant development, productivity and fruit quality from combinations of planting methods, nitrogen fertilizer applications and inoculation with Azospirillum brasilense in Cantaloupe melons cultivated in a protected environment. A randomized blocks design was adopted with a 2×2×2 factorial scheme with five replications. The treatments consisted of combinations of planting methods (pre-established seedlings or direct field sowing), inoculation with A. brasilense (with or without) and nitrogen fertilization (with and without). During the vegetative phase, the height, stem diameter, number and length of plant internodes and relative chlorophyll content were evaluated. Fifty-five days after planting, the leaf nitrogen content, leaf area and dry mass were measured. At harvest, the number of days between planting and harvesting was calculated, and the fresh weight, circumference, length, bark and pulp thickness and fruit productivity were evaluated. It was verified that A. brasilense did not affect any of the evaluated characteristics. On the other hand, direct field seed sowing decreased the production time and provided good plant development. However, the size and productivity of the fruits were higher when pre-established seedlings were used, with or without inoculation with A. brasilense, fertilized with nitrogen. It was concluded that the combinations of the different sowing methods, nitrogen fertilization and inoculation with A. brasilense affected the development and characteristics of the Cantaloupe melon plants and fruits.